Continuous training of the teacher/tutor in the skill of learning to learn in the university scenario - Satchimo Namalyongo, Apolinário; Urbay Rodríguez, Marilin (PEM. Revista de Didáctica, Evaluación e Innovación, 2024)
Continuing education for university teachers is a necessity for higher education in the Republic of Angola. The theoretical and practical deficiencies detected in this process and the need for the teacher/tutor to become a transformer of the pedagogical practice scenario, lead to determining as an objective of this research the proposal of a continuing education program for  teachers/tutors in the skill of learning to learn. The program is distinguished by the way its theoretical bases are structured with an integrative character, in which the continuing education of teachers/tutors is conceived in the transition through each of its stages, whose content grants it uniqueness from the determination of the criteria and learning sequences that allow reaching a level of mastery of this skill. Theoretical, empirical and statistical methods were applied to assess the initial diagnosis and the transformations achieved in the teacher/tutor in the context of the Higher Institute of Educational Sciences-Huambo-Angola, which corroborated the relevance of the proposal and the upward movement in the level of mastery of the learning to learn skill.
Keywords: continuing education; learning to learn skill; learning sequences